Matrix effects in Pb/U measurements during LA-ICP-MS analysis of the mineral apatite. Issue 6 (27th May 2016) - Thompson, Jay; Meffre, Sebastien; Maas, Roland; Kamenetsky, Vadim; Kamenetsky, Maya; Goemann, Karsten; Ehrig, Kathy; Danyushevsky, Leonid
Abstract : U–Pb ages of several apatite reference materials, acquired by LA-ICP-MS over a 3.5 year period using the Otter Lake apatite as a primary standard, show systematic offsets (up to 3%) from reference ages obtained by isotope dilution mass spectrometry. Abstract : U–Pb ages of several apatite reference materials, acquired by LA-ICP-MS over a 3.5 year period using the Otter Lake apatite as a primary standard, show systematic offsets (up to 3%) from reference ages obtained by isotope dilution mass spectrometry. The offsets are well outside known analytical errors from counting statistics, uncertainty in common Pb corrections or excess 206 Pb in high-Th/U materials. The age offsets also do not correlate strongly with the concentrations of F, Cl, REE, Th and U, with accumulated radiation dose or with the depth of ablation pits. We suggest that the observed age offsets are related to elemental fractionation at the ablation site, but their direction and magnitude cannot at present be predicted from compositional differences in different apatite samples. Our results further suggest that Otter Lake apatite is too heterogeneous for use as a calibration standard. Two other apatite samples, OD306 (1596.7 ± 7.1 Ma) and the 401 apatite (530.3 ± 1.5 Ma) are introduced as potential U–Pb reference materials.